Characterization and production optimization of a broad-spectrum bacteriocin produced by Lactobacillus casei KLDS 1.0338 and its application in soybean milk biopreservation. Issue 1 (1st January 2020) - Ma, Jiage; Yu, Wei; Hou, Juncai; Han, Xiue; Shao, Hong; Liu, Ying
ABSTRACT: This study aimed at characterization, production optimization, and assessing the biopreservative potential of a broad antimicrobial spectrum bacteriocin produced by Lactobacillus casei KLDS 1.0338, isolated from fermented sourdough in Northeast region of China. Ammonium sulfate precipitation and SP Sepharose TM fast flow were adopted to purify the bacteriocin, which resulted in a 7.43-fold purification and its molecular mass was estimated as 6.8 kDa. The bacteriocin was active over a wide pH range (2.0–12.0) and 2–12% NaCl and was heat and cold resistant (121°C for 30 min, and −20°C for 30 days). Optimization of culture conditions by response surface methodology indicated that the bacteriocin production was significantly enhanced than that of control ( P < 0.05). Moreover, the lyophilized antimicrobial substance inhibited the growth of Staphylococcus aureus and Penicilliu m sp. in fermented soybean milk during storage at 4°C for 21 days. These results demonstrated that the bacteriocin from L. casei KLDS 1.0338 is a potential candidate for controlling microbial contamination and extending the shelf life of food products.